Предмет: Алгебра, автор: Dark9800

Решите уравнения ,используя введение новой переменной:

Приложения:

Ответы

Автор ответа: Матов
0
frac{12}{x^2+x-10}   - frac{6}{x^2+x-6}= frac{5}{x^2+x-11}\
zamena\
x^2+x=a\
frac{12}{a-10} - frac{6}{a-6}= frac{5}{a-11}\
\
frac{12(a-6)-6(a-10)}{(a-10)(a-6)}= frac{5}{a-11}\
frac{12a-72-6a+60}{(a-10)(a-6)}= frac{5}{a-11}\
frac{6a-12}{(a-10)(a-6)} = frac{5}{a-11}\
frac{(a-11)(6a-12)}{(a-10)(a-6)} = frac{5(a-10)(a-6)}{(a-11)(a-10)(a-6)}\
(a-11)(6a-12)=5(a-10)(a-6)\
a^2+2a-168=0\
a=12\

a=-14\
\
x^2+x=12\
x^2+x-12=0\
D=1+4*1*12 = 7^2\
x_{1}=frac{-1+7}{2}=3\
x_{2}=frac{-1-7}{2}=-4\

 
Похожие вопросы